The Effect of Accounting Knowledge, Business Experience and Work Motivation on the Perception of Financial Report Usage - Ali, Fifitri; Rahmadayanti , Vivin (Lembaga Riset Ilmiah, 2024)
The purpose of this study was to examine the effect of work motivation, accounting knowledge and business experience on the use of accounting information for SMEs in Tegal Regency. This research is a type of quantitative research. The population used in this study was 385 SMEs in Tampan District. The sampling method used is purposive sampling. From these data obtained 118 respondents. The variables of this study consist of accounting knowledge, business experience), work motivation as independent variables, and perceptions of the use of financial statements as the dependent variable, with an ordinal measurement scale. The analytical method used is descriptive analysis, classical assumption test, multiple linear regression analysis, t test and coefficient of determination. The results of this study are accounting knowledge, business experience and work motivation have a significant effect on the perception of the use of financial reports.